Repeated COVID-19 relapse during post-discharge surveillance with viral shedding lasting for 67 days in a recovered patient infected with SARS-CoV-2 - Fang Liu; Zhao-bin Cai; Jin-song Huang; Hai-ying Niu; Wen-yan Yu; Yan Zhang; Ting-bo Yan; Chen Chen; Yuan Liu; Ai-fang Xu (Journal of Microbiology, Immunology and Infection, 2021)
A case who revealed the longest duration of viral shedding (67 days) in current reports, presented complicated characteristic on the relapse of COVID-19 due to the inconsistent performance of chest radiography and SARS-CoV-2-RNA detection after discharge. Lopinavir-interferon α2b boosted ribavirin following with lopinavir boosted budesonide might be a potent treatment for viral clearance.